THE RELATIONSHIP BETWEEN SECONDARY SCHOOL TEACHERS AND STUDENTS' READINESS OF USING FLIPPED CLASSROOM - Kazu, Ibrahim Yasar; Yalcin, Cemre Kurtoglu (Ceska Zemedelska Univ & Praze, 2022)
The emergence of instructional technologies has made inevitable changes in educational settings. The flipped classroom that integrates education with technology has grown in popularity in recent years. This study intends to investigate the relationship between secondary school teachers' and their students' flipped classroom readiness. Data were collected through a scale for flipped classroom readiness of teachers and their students. There were 745 participants randomly selected from 5th and 8th grade students and 233 teachers from five different secondary schools in Elazig, Turkey. It is concluded that teachers and students are generally ready to apply this model. Additionally, there is a positive relationship between teachers and their students' technology self-efficacy. Also, the students whose teachers are open-minded have more positive opinions on the flipped classroom. The study hopes to contribute to the increase in the usage of the flipped classroom in educational settings regarding both teachers' and their students' readiness. It has pedagogical implications for teachers to be trained and given more knowledge about the model so that the more the teacher is informed with the flipped classroom the more students can benefit.
Keywords: Flipped classroom readiness; flipped learning; planning classroom time; teaching and learning; technology-based learning